CIGARETTE SMOKE INDUCES PROTEASOMAL-MEDIATED DEGRADATION OF DNA METHYLTRANSFERASES AND METHYL CpG-/CpG DOMAIN-BINDING PROTEINS IN EMBRYONIC OROFACIAL CELLS - Mukhopadhyay, Partha (Reprod Toxicol, 2015)
Orofacial clefts, the most prevalent of developmental anomalies, occur with a frequency of 1 in 700 live births. Maternal cigarette smoking during pregnancy represents a risk factor for having a child with a cleft lip and/or cleft palate. Using primary cultures of first branchial arch-derived cells (1-BA cells), which contribute to the formation of the lip and palate, the present study addressed the hypothesis that components of cigarette smoke alter global DNA methylation, and/or expression of DNA methyltransferases (Dnmts) and various methyl CpG-binding proteins. Primary cultures of 1-BA cells, exposed to 80 μg/ml cigarette smoke extract (CSE) for 24 hrs, exhibited a >13% decline in global DNA methylation and triggered proteasomal-mediated degradation of Dnmts (DNMT-1, and - 3a), methyl CpG binding protein 2 (MeCP2) and methyl-CpG binding domain protein 3 (MBD-3). Pretreatment of 1-BA cells with the proteasomal inhibitor MG-132 completely reversed such degradation. Collectively, these data allow the suggestion of a potential epigenetic mechanism underlying maternal cigarette smoke exposure-induced orofacial clefting.